AN EXPERIMENTAL STUDY OF THE EFFECT OF SAGO PULP MESH SIZE ON THE MECHANICAL PROPERTIES OF COMPOSITES - Aufar Dhaifullah; I Iqbal; M Mahyuddin; M Muhtadin; Muhammad Faisal (Politeknik Negeri Lhokseumawe, 2026)
This study aims to analyze the effect of variations in the mesh size of sago pulp on the mechanical properties of polyester resin-based composites. Sago pulp was used as a reinforcing material with mesh sizes of 20, 30, and 40, and a composition of 40% sago pulp and 60% polyester resin. The method used was a laboratory experiment involving tensile, bending, and impact tests.Test results show that the 30-mesh size has the highest tensile strength of 2.76 kgf/mm², while the 20-mesh size exhibits the highest bending strength of 2.88 kgf/mm². The 40-mesh size yields the lowest strength values in most tests. These differences are influenced by particle distribution and the quality of the bond between the sago pulp and the resin.It is concluded that mesh size significantly affects the mechanical properties of the composite, and sago pulp composites have the potential to serve as a more environmentally friendly alternative to wood. Keywords: sago pulp, composite, mesh size, mechanical properties.